USING PROBLEM BASED LEARNING STRATEGY TO IMPROVING STUDENT’ VOCABULARY MASTERY - Puja Renita Meilani; Ahmad Talib; Chairil Anwar Korompot (International Journal of Business English and Communication, 2024)
This study aims to determine the use of problem-based learning (PBL) strategies can improve students' reading comprehension in English language learning. This study used a pre-experimental approach with a total sample of 15 students of class XI Kriya dan Kayu of SMKN 3 Gowa. In this study, data collection was carried out by conducting pre-test, post-test, and test. The results of data analysis showed that the use of problem-based learning strategies (PBL) can improve students' reading comprehension. This can be proven by the t-test value lower than P (0.000 < 0.05) which means that H0 of this study is rejected and H1 is accepted. So, it can be concluded that the use of problem-based learning (PBL) can improve students' reading comprehension in class XI of Kriya dan Kayu of SMKN 3 Gowa.